Gamma – irradiation induced degradation of diclofenac in aqueous solution: Kinetics, role of reactive species and influence of natural water parameters. Issue 2 (June 2016) - Nisar, Jan; Sayed, Murtaza; Khan, Farman Ullah; Khan, Hasan Mahmood; Iqbal, Munawar; Khan, Rafaqat Ali; Anas, Muhammad
Graphical abstract: Highlights: Degradation of diclofenac was assessed successfully in water by gamma irradiation. OH played important role in degradation of diclofenac. Second order rate constants of diclofenac with OH was measured. Organic and inorganic degradation by-products of diclofenac were detected. Abstract: Degradation of the anti-inflammatory drug diclofenac from aqueous media by means of gamma irradiation has been investigated. The results showed that concentration of diclofenac gradually decreased with increasing absorbed dose. When 4.5 mg L −1 aqueous solution of diclofenac was irradiated for an absorbed dose of 1015 Gy, nearly 97% degradation of diclofenac was achieved. The kinetic studies containing 4.5, 10.5, 14.0 and 18 mg L −1 of diclofenac showed that degradation of diclofenac decreased with increase in initial concentration of diclofenac and follows pseudo – first order kinetics. The initial pH value of the solution also affected the degradation efficiency of diclofenac. The degradation efficiency was higher in N2 O – saturated solution compared to aerated and N2 – saturated solutions. The radical scavengers like tert -butanol, iso -propanol as additives showed negative effect on the deagrdation of diclofenac. The quantitative role of reactive radical towards degradation of diclofenac was found to be in the order of OH > eaq − > H. The second order rate constant of OH radical with diclofenac was calculated to be 2.5 × 10 9 M −1 s −1 . The addition of various water parameters as additives like nitrite, nitrate, carbonate and bicarbonate restrained the degradation efficiency of diclofenac. The removal of total organic carbon (TOC) was higher in case of N2 O-saturated media than aerated and N2 -saturated media. The organic and inorganic byproducts like 2, 6-dicholorophenol, 4-chlorcatechol, hydroquinone, Cl −, NH4 +, CH3 COO − were qualitative and quantitavely determined.